Permanent draft genome sequence of Frankia sp. NRRL B-16219 reveals the presence of canonical nod genes, which are highly homologous to those detected in Candidatus Frankia Dg1 genome - Ktari, Amir (Stand Genomic Sci, 2017)
Frankia sp. NRRL B-16219 was directly isolated from a soil sample obtained from the rhizosphere of Ceanothus jepsonii growing in the USA. Its host plant range includes members of Elaeagnaceae species. Phylogenetically, strain NRRL B-16219 is closely related to “Frankia discariae” with a 16S rRNA gene similarity of 99.78%. Because of the lack of genetic tools for Frankia, our understanding of the bacterial signals involved during the plant infection process and the development of actinorhizal root nodules is very limited. Since the first three Frankia genomes were sequenced, additional genome sequences covering more diverse strains have helped provide insight into the depth of the pangenome and attempts to identify bacterial signaling molecules like the rhizobial canonical nod genes. The genome sequence of Frankia sp. strain NRRL B-16219 was generated and assembled into 289 contigs containing 8,032,739 bp with 71.7% GC content. Annotation of the genome identified 6211 protein-coding genes, 561 pseudogenes, 1758 hypothetical proteins and 53 RNA genes including 4 rRNA genes. The NRRL B-16219 draft genome contained genes homologous to the rhizobial common nodulation genes clustered in two areas. The first cluster contains nodACIJH genes whereas the second has nodAB and nodH genes in the upstream region. Phylogenetic analysis shows that Frankia nod genes are more deeply rooted than their sister groups from rhizobia. PCR-sequencing suggested the widespread occurrence of highly homologous nodA and nodB genes in microsymbionts of field collected Ceanothus americanus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40793-017-0261-3) contains supplementary material, which is available to authorized users.